Bell, Rose (audio interview #2 of 2) - Bell, Rose (b. 1904? - d. unknown); Feichtinger, Kris, interviewer
INTERVIEW DESCRIPTION - The circumstances of the interview are not known, particularly since Bell was a member of the ILGWU, not the ACWA, which was the focus of the interviews by Feichtinger. Another woman was present during the interview and often chimed in. TOPICS - union benefits; feminism; views on women's status; union activities; and union participation in Russia;family history; attitudes towards unionism; political climate in Russia; attitudes towards women and women's liberation movement; immigration to US; family life; parents; education; and gender roles; 1/4/1975